Spatiotemporal characteristics and socioeconomic inequalities in water, sanitation, and hygiene access in China from 2000 to 2020: analysis of data from three national censuses - Shaojie Li; Ailing Gong; Yongtian Yin; Qingxiang Su (BMC, 2024)
Abstract Background Access to water, sanitation, and hygiene (WASH) facilities presents a significant global public health challenge. This study aims to investigate the temporal and spatial characteristics of WASH access in mainland China, as well as the socioeconomic equity, using data from national censuses. Methods We analyzed households' data from three national censuses spanning 2000 to 2020 to examine the characteristics of safe water, sanitary toilets, and hygiene bathing facilities over time. Spatial clustering of WASH facilities in 2020 was assessed using Moran's I analysis. Socioeconomic disparities in WASH access across provinces were quantified using the Slope Index of Inequality (SII) and Relative Index of Inequality (RII). Results Between 2000 and 2020, access to safe water in China increased significantly from 45.7% to 91.3%, access to sanitary toilets rose from 18.7% to 78.5%, and access to hygiene bathing facilities climbed from 26.0% to 88.4%, reflecting continuous improvements in WASH access. Urban areas consistently outperformed rural areas, and the eastern region showed higher access rates compared to the central and western regions. Spatial analysis revealed statistically significant clustering of sanitary toilets and hygiene bathing facilities at the provincial level in 2020. Equity analysis indicated a notable improvement in the fairness of WASH access over the past two decades, with decreases observed in both SII and RII metrics. Conclusion Mainland China has made substantial strides in enhancing WASH access over the last 20 years, accompanied by significant improvements in provincial equity. However, persistent regional disparities underscore the need for targeted financial support to rural, central, and western regions to further enhance WASH accessibility.